The dress lodger - Holman, Sheri (New York : Ballantine Books, 2001)
In a novel set in London during the Industrial Revolution, a prostitute borrows a blue dress to attract a higher class of client and is shadowed through the streets by an evil old woman hired by the dress' owner to keep an eye on her.
2
Keywords: Sunderland (Tyne and Wear, England) -- Fiction; Teenage prostitution -- Fiction; Unmarried mothers -- Fiction; Single mothers -- Fiction; Body snatching -- Fiction; Prostitutes -- Fiction; Physicians -- Fiction; Body snatching -- Fiction; Body snatching; Physicians; Prostitutes; Single mothers; Teenage prostitution; Unmarried mothers; England -- Sunderland (Tyne and Wear); Historical fiction; Historical fiction; Fiction; Historical fiction; Historical fiction